Developing a new technique for determining service modularity level - Vestertė, Jurga; Skačkauskienė, Ilona (Journal of Business Economics and Management, 2022)
This paper addresses the existing methodological gap in assessing service modularity level. The study uses a qualitative approach and develops a technique to quickly and cost-effectively determine service modularity level. The theoretical framework builds on the principles of measurement theory, evaluation theory, and multicriteria analysis (MCA). To test the developed technique, an exploratory case study was conducted focusing on three service companies in Lithuania. Data were collected by interviewing key informants using the proposed instrument. The collected data were analysed and linked to the developed multidimensional scale for measuring the service modularity level. The obtained results support the view that qualitative evaluation can be an alternative for calculating modularity indices in the field of service modularity. The paper provides a practical tool for service modularity assessment for service industry practitioners to accelerate decision-making. The study contributes to the field of service modularity by delivering insights into assessing service modularity level. These insights are particularly important because the literature on measuring modularity level in services has been quite scarce.